2015
DOI: 10.1007/s10236-015-0875-1
|View full text |Cite
|
Sign up to set email alerts
|

Calculating residual flows through a multiple-inlet system: the conundrum of the tidal period

Abstract: The concept of residual, i.e., tidally-averaged, flows through a multiple inlet system is reappraised. The evaluation of the residual through-flow depends on the time interval over which is integrated, in other words, on how one defines the tidal period. It is demonstrated that this definition is ambiguous and that different definitions (based on, e.g., high waters, slack tides, etc.) yield very different results for the residual, also in terms of their long-term statistical properties (median and standard dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…[] that gaps in space and time in the ADCP ferry measurements make the calculation of the annual mean transport unreliable. Besides, the model results show a huge variability, even in sign, of the annual‐mean transport through the Marsdiep [ Duran‐Matute and Gerkema , ], as it depends strongly on the interannual variability of the wind statistics. As a result, it is not really meaningful to speak of “the” annual‐mean transport as such.…”
Section: Model Skill Assessmentmentioning
confidence: 99%
“…[] that gaps in space and time in the ADCP ferry measurements make the calculation of the annual mean transport unreliable. Besides, the model results show a huge variability, even in sign, of the annual‐mean transport through the Marsdiep [ Duran‐Matute and Gerkema , ], as it depends strongly on the interannual variability of the wind statistics. As a result, it is not really meaningful to speak of “the” annual‐mean transport as such.…”
Section: Model Skill Assessmentmentioning
confidence: 99%
“…Several studies showed that wind and rainfall affect the hydrodynamics of the Wadden Sea substantially (Donker, 2015;Duran-Matute et al, 2014;Duran-Matute & Gerkema, 2015). Duran-Matute et al (2014) found how wind can change the advective transport.…”
Section: Future Budgetsmentioning
confidence: 99%
“…This definition was first introduced by Duran‐Matute et al . [], and its advantages were further discussed by Duran‐Matute and Gerkema [].…”
Section: Numerical Setup and Computation Of Tidally Averaged Quantitiesmentioning
confidence: 99%
“…We define the tidal period as the time between two consecutive instants, taken during rising tides, when the instantaneous water volume inside the WDWS matches the long-term average value. This definition was first introduced by Duran-Matute et al [2014], and its advantages were further discussed by Duran-Matute and Gerkema [2015].…”
Section: Numerical Setup and Computation Of Tidally Averaged Quantitiesmentioning
confidence: 99%
See 1 more Smart Citation